Monumental Painting of Prilep (North Macedonia): A View on Provincial Byzantine Art of the Second Half of the 13th Century - Dyatlova, Elena S. (Actual Problems of Theory and History of Art, 2021)
The paper analyses the key stylistic trends of the second part of the 13th century murals in Prilep, North Macedonia in wider context of early Palaiologan art. Stylistic parallels in contemporary Byzantine monuments in Northern Greece, Epirus, and Serbia highlight tight artistic connections of this border town of newly revived Byzantine Empire not only with Serbian kingdom, as it was pointed out by previous Macedonian researches, but also with the Despotate of Epirus. Following the tradition of Epirus, the masters of the workshop of the deacon and referendarius John, who worked in Prilep in the second half of the 13th century, intentionally averted to the Komnenian art as a visual part of the great past of the Byzantine Empire. On the other hand, they were also following the new monumental trends from the metropolitan artistic circles, which also came from the orientation on classical art in its plastic form. Different combinations of these two trends determined the stylistic character of the Byzantine art in North Macedonia in the second half of the 13th century. This research has been completed with the support of the Russian Science Foundation (RSF), project № 20-18-00294.